1995
DOI: 10.1128/jcm.33.5.1253-1257.1995
|View full text |Cite
|
Sign up to set email alerts
|

Potential sources of sporadic human infection with Yersinia enterocolitica serovar O:8 in Aomori Prefecture, Japan

Abstract: contents from 204 small mammals living in the wild were collected and examined for the presence of Yersinia enterocolitica serovar O:8 to clarify the source of human infections caused by this microbe in the Tsugaru Region of Aomori Prefecture, Japan. Serovar O:8 was isolated from 10 (5.2%) of 193 wild rodents trapped in June 1993 (9 of 107) and August 1993 (1 of 23) but not from animals trapped in November 1992 (0 of 63). This serovar was not isolated from 11 moles. From May to September 1993, 12 human patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Yersinia outbreaks in breeding monkeys have also been reported in Japan, but all reported outbreaks were of Y. pseudotuberculosis (15,21,27,29,34,39). Therefore, the present study indicates the need for more attention to the possibility of the occurrence of Y. enterocolitica serovar O:8 outbreaks, especially in countries such as the United States and Japan, where reservoirs of this serovar are found in nature (1,8,13,18,19,22,33,35).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Yersinia outbreaks in breeding monkeys have also been reported in Japan, but all reported outbreaks were of Y. pseudotuberculosis (15,21,27,29,34,39). Therefore, the present study indicates the need for more attention to the possibility of the occurrence of Y. enterocolitica serovar O:8 outbreaks, especially in countries such as the United States and Japan, where reservoirs of this serovar are found in nature (1,8,13,18,19,22,33,35).…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, although a human case of Y. enterocolitica serovar O:8 infection was reported in 1997, in Kanagawa Prefecture (16), located at the south of the Kanto region that lies in the central part of Honshu island, isolation of this pathogen from rodents has been reported only in wild rodents of the north area of Honshu island (13,19). This study showed the presence of this pathogen in black rats living in the Kanto region, indicating that serovar O:8 strains are also present in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Y. enterocolitica 4/O:3 is the most frequently isolated bioserotype from domestic pigs (Table and ), but not from wild animals captured outside farms other than wild boar (Aldová and Lim ; Zen‐Yoji and others ; Tsubokura and others ; Kapperud , ; Bercovier and others ; Kaneko and others ; Servan and others ; Kapperud and Rosef ; Fukushima and others , ; Kato and others ; Glünder and others ; Shayegani and others ; Kaneuchi and others , ; Iinuma and others ; Cork and others 1993; Hayashidani and others , ; Lysý and Ürgeová ; Suzuki and others ; Pocock and others ; Niskanen and others ; Milnes and others ; Fredriksson‐Ahomaa and others 2004; Wacheck and others ; Sannö and others ). Usually the genetic type of the strains isolated from wild boars differs from those isolated from domestic pigs (Fredriksson‐Ahomaa and others ).…”
Section: Enteropathogenic Yersinia On Pig Farmsmentioning
confidence: 99%
“…In 1991, Ichinohe et al reported the first case of Y. enterocolitica serotype O:8 infection in northern Japan (Hirosaki city in Aomori Prefecture) (7), and only sporadic cases, limited to this area, have been reported subsequently (6,20). Therefore, serotype O:8 infection is still uncommon in Japan.…”
mentioning
confidence: 99%
“…Food-borne transmission of Y. enterocolitica has been suggested; however, a specific food has not been determined for our patient. Furthermore, the patient had not been exposed to small rodents, which are considered to be carriers of this pathogen in Japan (6,8,21), and had not traveled to Aomori Prefecture.…”
mentioning
confidence: 99%